Integrasi Data Pemeriksaan Geometri dan Estimasi Waktu–Biaya pada Perencanaan Pemeliharaan Jembatan Jalan Tol Layang MBZ - Dian Dian; Mardiaman Mardiaman; Hikma Dewita (Universitas Batanghari Jambi, 2026)
Condition-based bridge maintenance requires the integration of information on the actual structural condition, implementation time, and costs to ensure effective and efficient infrastructure asset management. This study aims to analyze the integration of geometric inspection data with time and cost estimates in the maintenance planning of the Sheikh Mohammed Bin Zayed (MBZ) Elevated Toll Road Bridge. The study employed a qualitative approach with a case study design. Secondary data were obtained from the contractor, including geometric measurement results collected using a Robotic Total Station (RTS), dual-frequency geodetic GPS, and a digital level, as well as the Bill of Quantities (BoQ), project schedule, and other technical documents. Data were collected through document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The results show that geometric inspection data can be integrated with project schedule and budget information within a unified maintenance-planning information framework. The geometric inspection, data processing, and preparation of the maintenance plan were completed within 90 calendar days at a total cost of IDR 965,061,750. The integration of geometric, time, and cost data provides more structured planning information to support the implementation of condition-based maintenance. However, the integration remains at the planning-information level and does not yet establish a quantitative relationship between geometric changes and the type, volume, duration, and cost of physical repair works. This study strengthens the application of condition-based maintenance and integrated asset management and provides practical implications for toll road operators in improving planning accuracy and bridge maintenance efficiency.